Transition metal compound, catalyst composition, olefin polymerization method and application

By using transition metal compounds with specific structures and their catalyst compositions, the problem of insufficient activity of the existing catalyst is solved, and efficient olefin polymerization is achieved to generate a uniform polymer.

CN119143793APending Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310715950.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

There is room for further improvement in the catalytic activity of existing non-locene transition metal catalysts, and it is difficult to meet the needs of high efficiency and broad spectrum in the polymerization process of olefins.

Method used

A transition metal compound and a catalyst composition thereof are provided, including a combination of tetravalent transition metal atoms of a specific structure and a cocatalyst component such as alkyl aluminoxanes, organoboron compounds and organoaluminum compounds, for use in olefin polymerization.

Benefits of technology

The catalytic activity is significantly improved, and high-efficiency olefin polymerization can be achieved at lower concentrations and suitable temperatures, resulting in polymers with uniform molecular weight distribution and chemical composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143793A_ABST
    Figure CN119143793A_ABST
Patent Text Reader

Abstract

The invention relates to the field of olefin polymerization, and discloses a transition metal compound, a catalyst composition using the transition metal compound, an olefin polymerization method using the catalyst composition, and an application of the transition metal compound or the catalyst composition in olefin polymerization. The structure of the transition metal compound is shown in the formula (1), and in the formula (1), M is a tetravalent transition metal atom; x and Y are respectively and independently alkyloxy with the carbon atom number of 1-10, alkyl with the carbon atom number of 1-10 or halogen. The catalyst composition provided by the invention has the advantage of high catalytic activity. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of olefin polymerization, and in particular, to a transition metal compound, a catalyst composition using the transition metal compound, an olefin polymerization method using the catalyst composition, and application of the transition metal compound or the catalyst composition in olefin polymerization. Background Art

[0002] Single-site catalysts for olefin polymerization have been a research hotspot in organometallic chemistry, catalysis, polymer chemistry, and materials science in recent decades. Using this type of catalyst, olefin polymers with uniform molecular weight distribution and chemical composition distribution can be obtained, and the molecular structure and molecular weight of the polymer can be highly controllable by adjusting the catalyst structure. Since this type of catalyst is highly efficient and broad-spectrum when applied to olefin copolymerization (ChemistrySelect 2020, 5, 7581-7585), olefin polymers that cannot be obtained with traditional Ziegler-Natta catalysts can be obtained by using this type of catalyst.

[0003] Non-metallocene transition metal catalysts are important components of single-site catalysts. They have rich ligand structures and simple synthesis processes. Their catalytic performance can be easily adjusted by adjusting the ligand structure (Chemical Reviews, 2003, 103, 283-315).

[0004] There is still room for further improvement in the catalytic activity of non-transition metallocene catalysts in the prior art. Summary of the invention

[0005] The object of the present invention is to provide a new transition metal compound, a catalyst composition using the transition metal compound, an olefin polymerization method using the catalyst composition, and the use of the transition metal compound or the catalyst composition in olefin polymerization. By using the catalyst composition of the present invention, the catalyst has the advantage of high catalytic activity.

[0006] In order to achieve the above object, the present invention provides a transition metal compound, wherein the structure of the transition metal compound is as shown in the following formula (1):

[0007]

[0008] In formula (1), M is a tetravalent transition metal atom; X and Y are each independently a hydrocarbyloxy group having 1 to 10 carbon atoms, a hydrocarbon group having 1 to 10 carbon atoms, or a halogen.

[0009] Preferably, M is a titanium atom, a zirconium atom or a hafnium atom, more preferably a titanium atom or a zirconium atom.

[0010] Preferably, X and Y are each independently a hydrocarbyloxy group having 1 to 6 carbon atoms, a hydrocarbyl group having 1 to 7 carbon atoms, a fluorine atom, a chlorine atom, a bromine atom or an iodine atom.

[0011] Preferably, X and Y are each independently a hydrocarbyloxy group having 1 to 3 carbon atoms, a hydrocarbon group having 1 to 3 carbon atoms, or a chlorine atom.

[0012] Preferably, the alkoxy group having 1 to 10 carbon atoms is methoxy, ethoxy, propoxy or isopropoxy.

[0013] Preferably, the hydrocarbon group having 1 to 10 carbon atoms is methyl, ethyl, propyl, isopropyl or benzyl.

[0014] Preferably, X and Y are both isopropoxy or ethoxy; or, X and Y are both chlorine atoms.

[0015] According to a second aspect of the present invention, a catalyst composition is provided, wherein the catalyst composition comprises the following composition:

[0016] a) the transition metal compound according to the first aspect of the present invention;

[0017] b) Co-catalyst component.

[0018] Preferably, the co-catalyst component comprises an alkylaluminoxane, a combination of an organoboron compound and an organoaluminum compound, or a combination of an organoaluminum compound and an organomagnesium compound.

[0019] Preferably, the co-catalyst component is an alkylaluminoxane, a combination of an organic boron compound and an organic aluminum compound, or a combination of an organic aluminum compound and an organic magnesium compound.

[0020] Preferably, the alkylaluminoxane is a compound selected from the structure represented by formula (2) and / or formula (3),

[0021]

[0022] In formula (2) and formula (3), R is selected from an alkyl group having 1 to 15 carbon atoms, and n represents an integer of 4 to 30; more preferably, R is selected from an alkyl group having 1 to 5 carbon atoms, and n represents an integer of 10 to 30; further preferably, the alkylaluminoxane is methylaluminoxane.

[0023] Preferably, the organic boron compound is one or more of triphenylmethyl tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and tris(pentafluorophenyl)boron.

[0024] Preferably, the organoaluminum compound is a compound having a structure represented by the general formula AlX1X2X3, wherein X1, X2 and X3 are respectively a halogen atom, an alkyl group having 1-8 carbon atoms, an alkoxy group having 1-8 carbon atoms, and an aryloxy group having 6-12 carbon atoms, and X1, X2 and X3 may be the same or different, and at least one is an alkyl group having 1-8 carbon atoms.

[0025] Preferably, the organoaluminum compound is triisobutylaluminum.

[0026] Preferably, the organic magnesium compound is an organic magnesium compound containing two alkyl groups with carbon atoms of 1-10, preferably an organic magnesium compound containing two alkyl groups with carbon atoms of 1-6, and more preferably di-n-butyl magnesium.

[0027] Preferably, the co-catalyst component is alkylaluminoxane, and the molar ratio of the transition metal compound to the alkylaluminoxane calculated as aluminum is 1:(100-20000), preferably 1:(200-10000), and more preferably 1:(500-5000).

[0028] Preferably, the co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, the molar ratio of the transition metal compound to the organic boron compound is 1:(1-5), preferably 1:(1-2), and the molar ratio of the transition metal compound to the organic aluminum compound is 1:(10-5000), preferably 1:(50-1000), and more preferably 1:(100-500).

[0029] Preferably, the co-catalyst component is a combination of an organic aluminum compound and an organic magnesium compound, the molar ratio of the transition metal compound to the organic aluminum compound is 1:(30-5000), preferably 1:(100-1000), more preferably 1:(100-500), and the molar ratio of the transition metal compound to the organic magnesium compound is 1:(10-2000), preferably 1:(100-1000).

[0030] Preferably, the molar ratio of the organoaluminum compound to the organomagnesium compound is greater than 2.5:1.

[0031] According to a third aspect of the present invention, there is provided a method for olefin polymerization, wherein the method comprises contacting an olefin with the catalyst composition according to the second aspect of the present invention to carry out a polymerization reaction.

[0032] Preferably, the concentration of the transition metal compound in the polymerization reaction system is 1×10 -10 mol / L~1×10 -3 mol / L, preferably 1×10 -8 mol / L~1×10 -5 mol / L.

[0033] Preferably, the polymerization temperature is -50 to 200° C., and the polymerization time is 1 to 300 minutes; more preferably, the polymerization temperature is -20 to 150° C., and the polymerization time is 5 to 60 minutes.

[0034] Preferably, the partial pressure of the olefin is 0.1-10 MPa, preferably 0.1-4.0 MPa.

[0035] According to a fourth aspect of the present invention, there is provided use of the transition metal compound described in the first aspect of the present invention or the catalyst composition described in the second aspect of the present invention in olefin polymerization.

[0036] Through the above technical solution, the catalyst composition using the transition metal compound has the advantage of high catalytic activity. DETAILED DESCRIPTION

[0037] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0038] The first aspect of the present invention provides a transition metal compound, wherein the structure of the transition metal compound is shown in the following formula (1):

[0039]

[0040] In formula (1), M is a tetravalent transition metal atom; X and Y are each independently a hydrocarbyloxy group having 1 to 10 carbon atoms, a hydrocarbon group having 1 to 10 carbon atoms, or a halogen.

[0041] According to the transition metal compound of the present invention, in formula (1), M is a tetravalent transition metal atom, preferably, M is a titanium atom, a zirconium atom or a hafnium atom; more preferably, M is a titanium atom or a zirconium atom.

[0042] According to the transition metal compound of the present invention, in formula (1), X and Y are each independently a hydrocarbyloxy group having 1 to 10 carbon atoms, a hydrocarbyl group having 1 to 10 carbon atoms, or a halogen; preferably, X and Y are each independently a hydrocarbyloxy group having 1 to 6 carbon atoms, a hydrocarbyl group having 1 to 7 carbon atoms, a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom; more preferably, X and Y are each independently a hydrocarbyloxy group having 1 to 3 carbon atoms, a hydrocarbyl group having 1 to 7 carbon atoms, or a chlorine atom.

[0043] Examples of the hydrocarbonoxy group having 1 to 10 carbon atoms include methoxy, ethoxy, propoxy, isopropoxy, butoxy, tert-butoxy, sec-butoxy, isobutoxy, pentyloxy, and hexyloxy. Among them, methoxy, ethoxy, propoxy, and isopropoxy are preferred, ethoxy, propoxy, and isopropoxy are more preferred, and ethoxy and isopropoxy are still more preferred.

[0044] As the hydrocarbon group having 1 to 10 carbon atoms, for example, methyl, ethyl, propyl, isopropyl, butyl, pentyl, hexyl or benzyl can be mentioned. Among them, methyl, ethyl, propyl, isopropyl or benzyl is preferred, and ethyl, isopropyl or benzyl is more preferred.

[0045] Examples of the halogen atom include fluorine, chlorine, bromine and iodine, preferably fluorine, chlorine or bromine, more preferably chlorine or bromine, and particularly preferably chlorine.

[0046] In a particularly preferred embodiment of the present invention, X and Y are both isopropoxy or ethoxy.

[0047] In another particularly preferred embodiment of the present invention, X and Y are both chlorine atoms.

[0048] As specific transition metal compounds, preferably the following compounds can be mentioned:

[0049] In formula (1), M is a titanium atom, and X and Y are both isopropoxy groups;

[0050] In formula (1), M is a titanium atom, and X and Y are both ethoxy groups;

[0051] In formula (1), M is a titanium atom, and X and Y are both chlorine atoms;

[0052] In formula (1), M is a titanium atom, and X and Y are both benzyl groups;

[0053] In formula (1), M is a zirconium atom, and X and Y are both isopropoxy groups;

[0054] In formula (1), M is a zirconium atom, and X and Y are both ethoxy groups;

[0055] In formula (1), M is a zirconium atom, and X and Y are both chlorine atoms;

[0056] In formula (1), M is a zirconium atom, and X and Y are both benzyl groups;

[0057] In formula (1), M is a hafnium atom, and X and Y are both isopropoxy groups;

[0058] In formula (1), M is a hafnium atom, and X and Y are both ethoxy groups;

[0059] In formula (1), M is a hafnium atom, and X and Y are both chlorine atoms;

[0060] In formula (1), M is a hafnium atom, and X and Y are both benzyl groups.

[0061] In the present invention, the transition metal compound can be synthesized according to conventional methods in the art. In a preferred embodiment of the present invention, when X and Y in formula (1) are each independently a hydrocarbonoxy group having 1 to 10 carbon atoms or a hydrocarbon group having 1 to 10 carbon atoms, the preparation method of the transition metal compound comprises: in an inert atmosphere and in the presence of a first organic solvent, a first contact reaction is carried out between 10-hydroxybenzo[H]quinoline and a compound represented by the general formula MA4 (hereinafter referred to as method 1).

[0062] In method 1, in the compound represented by the general formula MA4, M is a tetravalent transition metal atom; and A is independently a hydrocarbonoxy group having 1 to 10 carbon atoms or a hydrocarbon group having 1 to 10 carbon atoms.

[0063] Preferably, M is a titanium atom, a zirconium atom or a hafnium atom, more preferably a titanium atom or a zirconium atom.

[0064] Preferably, each A is independently a hydrocarbyloxy group having 1 to 6 carbon atoms or a hydrocarbyl group having 1 to 7 carbon atoms; more preferably, each A is independently a hydrocarbyloxy group having 1 to 3 carbon atoms or a hydrocarbyl group having 1 to 3 carbon atoms.

[0065] Preferably, the alkyloxy group having 1 to 10 carbon atoms is methoxy, ethoxy, propoxy or isopropoxy.

[0066] Preferably, the hydrocarbon group having 1 to 10 carbon atoms is methyl, ethyl, propyl, isopropyl or benzyl.

[0067] In method 1, the molar ratio of 10-hydroxybenzo[H]quinoline to the compound represented by the general formula MA4 can be 1.8-2.2:1, preferably 1.9-2.1:1, and more preferably 1.95-2.05:1.

[0068] In method 1, the first organic solvent may be an organic solvent that is inert to the reaction raw materials and can dissolve the reaction raw materials, for example, toluene may be used. The amount of the organic solvent may be selected according to the amount of 10-hydroxybenzo[H]quinoline, for example, the amount of the first organic solvent relative to 1 mol of 10-hydroxybenzo[H]quinoline is 5-30 L, preferably 6-20 L, more preferably 7-15 L, and particularly preferably 8-10 L.

[0069] In method 1, the inert atmosphere may be implemented by using nitrogen gas and / or argon gas.

[0070] In method 1, the conditions of the first contact reaction can be selected according to the boiling point of the first organic solution used, for example, the reaction can be carried out under reflux conditions for 5-20 hours, preferably 5-10 hours.

[0071] In method 1, after the first contact reaction is completed, the product may be purified by a conventional purification method in the art. For example, after the first contact reaction is completed, the solvent may be removed and washing may be performed to obtain the target product.

[0072] In a preferred embodiment of the present invention, after the first contact reaction is completed, the solvent is removed, and then centrifugal washing is performed 2-3 times using ice-cold hexane to obtain the target product.

[0073] In addition, when X and Y in formula (1) are each independently a halogen, the preparation method of the transition metal compound comprises: in an inert atmosphere and in the presence of a second organic solvent, subjecting 10-hydroxybenzo[H]quinoline to a second contact reaction with an n-butyllithium solution, and then subjecting it to a third contact reaction with a compound represented by MX4 (hereinafter referred to as method 2).

[0074] In method 2, in the compound represented by the general formula MX4, M is a tetravalent transition metal atom; and X is independently a halogen.

[0075] Preferably, M is a titanium atom, a zirconium atom or a hafnium atom, more preferably a titanium atom or a zirconium atom.

[0076] Examples of the halogen atom include fluorine, chlorine, bromine and iodine, preferably fluorine, chlorine or bromine, more preferably chlorine or bromine, and particularly preferably chlorine.

[0077] In method 2, the molar ratio of 10-hydroxybenzo[H]quinoline to n-butyllithium can be 1:0.95-1.5, preferably 1:1-1.2, and more preferably 1:1-1.1.

[0078] As the above-mentioned n-butyl lithium solution, for example, n-butyl lithium hexane solution can be used. When used in the form of a solution, the content of n-butyl lithium in the solution can be, for example, 1-3 mol / L, preferably 2-3 mol / L, and more preferably 2-2.5 mol / L.

[0079] In method 2, the second organic solvent may be an organic solvent that is inert to the reaction raw materials and can dissolve the reaction raw materials, for example, toluene may be used. The amount of the organic solvent may be selected according to the amount of 10-hydroxybenzo[H]quinoline, for example, relative to 1 mol of 10-hydroxybenzo[H]quinoline, the amount of the first organic solvent is 5-30 L, preferably 6-20 L, more preferably 7-15 L, and particularly preferably 7-9 L.

[0080] In method 2, the inert atmosphere may be implemented by using nitrogen and / or argon.

[0081] In method 2, the second contact reaction is preferably carried out by dropwise adding an n-butyl lithium solution into a mixed solution of 10-hydroxybenzo[H]quinoline and the second organic solvent.

[0082] The temperature of the second contact reaction during the dropwise addition may be -30 to 0° C., preferably -20 to -10° C. After the dropwise addition is completed, the reaction may be carried out at room temperature (eg, 10 to 40° C.) for 5 to 36 hours, preferably 12 to 24 hours.

[0083] In method 2, the molar ratio of 10-hydroxybenzo[H]quinoline to the compound represented by the general formula MX4 can be 1.8-2.2:1, preferably 1.9-2.1:1, and more preferably 1.95-2.05:1.

[0084] In method 2, the third contact reaction is preferably carried out by dropwise adding the n-butyllithium solution into the product of the first contact reaction to carry out the third contact reaction.

[0085] The temperature of the third contact reaction during the dropwise addition may be -30 to 0° C., preferably -20 to -10° C. After the dropwise addition is completed, the reaction may be carried out at room temperature (eg, 10 to 40° C.) for 5 to 36 hours, preferably 12 to 24 hours.

[0086] In method 2, after the third contact reaction is completed, the product may be purified by a conventional purification method in the art. For example, after the third contact reaction is completed, the solvent may be removed and washing may be performed to obtain the target product.

[0087] In a preferred embodiment of the present invention, after the third contact reaction is completed, a solid phase is obtained by solid-liquid separation, and centrifugation washing is performed 2-3 times using ice-cold hexane to obtain the target product.

[0088] In addition, in the present invention, the target product in method 2 can be prepared by replacing the hydrocarbonoxy group with 1-10 carbon atoms or the hydrocarbon group with 1-10 carbon atoms in the target product obtained by method 1 with a halogen group; similarly, the target product in method 2 can be prepared by replacing the halogen group with a hydrocarbonoxy group with 1-10 carbon atoms or the hydrocarbon group with 1-10 carbon atoms. The specific method can be implemented by conventional synthesis methods in the art.

[0089] According to a second aspect of the present invention, a catalyst composition is provided, wherein the catalyst composition comprises the following composition:

[0090] a) the transition metal compound according to the first aspect of the present invention;

[0091] b) Co-catalyst component.

[0092] According to the catalyst composition of the present invention, the co-catalyst component can be various co-catalyst components commonly used in the art. Preferably, the co-catalyst component includes a combination of alkylaluminoxane, an organoboron compound and an organoaluminum compound, or a combination of an organoaluminum compound and an organomagnesium compound; more preferably, the co-catalyst component is a combination of alkylaluminoxane, an organoboron compound and an organoaluminum compound, or a combination of an organoaluminum compound and an organomagnesium compound.

[0093] In a particularly preferred embodiment of the present invention, the co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, thereby significantly improving the catalytic activity.

[0094] The alkylaluminoxane is preferably a compound selected from the group consisting of compounds represented by formula (2) and / or formula (3).

[0095]

[0096] In formula (2) and formula (3), R is selected from an alkyl group having 1 to 15 carbon atoms, and n is an integer of 4 to 30; more preferably, R is selected from an alkyl group having 1 to 5 carbon atoms, and n is an integer of 10 to 30.

[0097] Specific examples of the above-mentioned alkyl group include methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, sec-butyl, isobutyl, pentyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, neopentyl, 1-methylbutyl, 2-methylbutyl, isopentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl and pentadecyl.

[0098] Examples of n include 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, and 30.

[0099] Specific examples of the alkylaluminoxane include methylaluminoxane, ethylaluminoxane, propylaluminoxane and the like, and among them, methylaluminoxane is preferred.

[0100] According to the catalyst composition of the present invention, the organic boron compound can be various organic boron compounds used as co-catalysts in the art, for example, one or more of triphenylmethyl tetrakis(pentafluorophenyl)borate, N,N-dimethylaniline tetrakis(pentafluorophenyl)borate and tris(pentafluorophenyl)boron.

[0101] According to the catalyst composition of the present invention, the organoaluminum compound can be various organoaluminum compounds used as co-catalysts in the art. Preferably, the organoaluminum compound is a compound with a general formula of AlX1X2X3, wherein X1, X2 and X3 are respectively a halogen atom, an alkyl group with 1-8 carbon atoms, an alkoxy group with 1-8 carbon atoms, and an aryloxy group with 6-12 carbon atoms, and X1, X2 and X3 can be the same or different, and at least one is an alkyl group with 1-8 carbon atoms.

[0102] Examples of the alkyl group having 1 to 8 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, sec-butyl, isobutyl, pentyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, neopentyl, 1-methylbutyl, 2-methylbutyl, isopentyl, hexyl, heptyl, and octyl.

[0103] Examples of the alkoxy group having 1 to 8 carbon atoms include various alkoxy groups having the above-mentioned "alkyl group having 1 to 8 carbon atoms" specifically exemplified.

[0104] Examples of the halogen atom include fluorine, chlorine, bromine and iodine, preferably fluorine, chlorine or bromine, more preferably chlorine or bromine, and particularly preferably chlorine.

[0105] In the present invention, specific examples of the organic aluminum compound include: one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tri-n-pentylaluminum, triisopentylaluminum, trihexylaluminum, ethyldimethylaluminum, methyldiethylaluminum, tripentylaluminum, diethylaluminum chloride and dimethylaluminum chloride.

[0106] In the present invention, when the co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, specific examples of the organic aluminum compound include: one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tri-n-pentylaluminum, triisopentylaluminum, trihexylaluminum, ethyldimethylaluminum, methyldiethylaluminum and tripentylaluminum. Among them, triisobutylaluminum is preferably used.

[0107] In the present invention, when the co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, the organoaluminum compound preferably contains at least one hydrocarbon group and at least one halogen atom, more preferably dialkylaluminum chloride, further preferably diethylaluminum chloride or dimethylaluminum chloride.

[0108] In the present invention, the organoaluminum-magnesium compound is preferably an organomagnesium compound containing two alkyl groups with carbon atoms of 1 to 10, and more preferably an organomagnesium compound containing two alkyl groups with carbon atoms of 1 to 6. For example, dimethylmagnesium, diethylmagnesium, di-n-propylmagnesium, di-n-butylmagnesium, di-n-pentylmagnesium, di-n-hexylmagnesium, etc. are mentioned, among which di-n-propylmagnesium, di-n-butylmagnesium and di-n-pentylmagnesium are preferably one or more, and di-n-butylmagnesium is more preferably.

[0109] According to the catalyst composition of the present invention, when the co-catalyst component is alkylaluminoxane, the molar ratio of the transition metal compound to the alkylaluminoxane calculated as aluminum is 1:(100-20000), preferably 1:(200-10000), and more preferably 1:(500-5000).

[0110] When the co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, the molar ratio of the transition metal compound to the organic boron compound is 1:(1-5), preferably 1:(1-2), and the molar ratio of the transition metal compound to the organic aluminum compound is 1:(10-5000), preferably 1:(50-1000), and more preferably 1:(100-500).

[0111] When the co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, the molar ratio of the transition metal compound to the organoaluminum compound is 1:(30-5000), preferably 1:(100-1000), more preferably 1:(100-500), and the molar ratio of the transition metal compound to the organomagnesium compound is 1:(10-2000), preferably 1:(100-1000). In addition, the molar ratio of the organoaluminum compound to the organomagnesium compound is preferably greater than 2.5:1.

[0112] According to a third aspect of the present invention, there is provided an olefin polymerization method, which comprises contacting an olefin with the catalyst composition according to the second aspect of the present invention to carry out a polymerization reaction.

[0113] According to the method of the present invention, preferably, the concentration of the transition metal compound in the polymerization reaction system is 1×10 -10 mol / L~1×10 -3 mol / L, preferably 1×10 -8 mol / L~1×10 -5 mol / L.

[0114] According to the method of the present invention, preferably, the polymerization reaction is carried out in an inert organic solvent. The inert organic solvent may be a mixture of one or more of a straight-chain aliphatic hydrocarbon, a branched aliphatic hydrocarbon, a substituted or unsubstituted cyclic aliphatic hydrocarbon, a substituted or unsubstituted aromatic hydrocarbon. Specific examples of the inert organic solvent include: hexane, heptane, cyclohexane, cyclooctane, toluene, and xylene. In addition, the amount of the organic solvent may be determined according to the reaction activity to ensure that the produced polymer is well dissolved in the system, at least without affecting the dispersion.

[0115] According to the method of the present invention, the polymerization reaction conditions can be the conditions commonly used in the field for synthesizing polyolefins. Preferably, the polymerization reaction temperature is -50 to 200°C, and the polymerization reaction time is 1 to 300 minutes; more preferably, the polymerization reaction temperature is -20 to 150°C, and the polymerization reaction time is 5 to 60 minutes.

[0116] According to the method of the present invention, preferably, the partial pressure of the olefin is 0.1-10 MPa, preferably 0.1-4.0 MPa.

[0117] According to the method of the present invention, the amount of olefin added may be, for example, 1,000-1,000,000 molar equivalent of the catalyst.

[0118] According to the method of the present invention, the olefin may be ethylene, propylene, etc.

[0119] According to a fourth aspect of the present invention, there is provided use of the transition metal compound described in the first aspect of the present invention or the catalyst composition described in the second aspect of the present invention in olefin polymerization.

[0120] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0121] The raw materials used in the following examples and comparative examples, unless otherwise specified, are all disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation method disclosed in the prior art.

[0122] Example 1

[0123] Synthesis of compound (1):

[0124]

[0125] Place the magnet in a dry 250 ml three-necked flask, and place the reaction flask on a device with magnetic stirring and oil bath heating. After evacuating the three-necked flask, rinse it repeatedly with nitrogen three times, add 470 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve; add 10 ml of toluene solution of tetra(isopropoxy)titanium (containing 342 mg of tetra(isopropoxy)titanium) and stir evenly. Then, under nitrogen protection, add a condenser with room temperature water as the cooling medium. Control the oil bath temperature at 115-130°C and allow the reaction to proceed for 8 hours under toluene reflux. Then remove the reflux condenser, install a distillation device, maintain the temperature, and evaporate the liquid of the reaction mixture until a yellow solid or viscous substance is obtained, and then cool it to room temperature. Under nitrogen protection, add 10 ml of cold hexane, mix thoroughly, and centrifuge the resulting slurry. Pour out the supernatant. Add 10 ml of cold hexane again, mix thoroughly, and centrifuge the resulting slurry. The supernatant was poured off, and the solvent of the obtained solid was removed under vacuum to obtain 641 mg of bright yellow solid with a molar yield of 96%.

[0126] 1 H-NMR(in CDCl3,d=):9.09-9.11(2H),7.71-7.73(2H),7.52-7.56(2H),7.46-7.49 (2H),7.14-7.19(6H),6.89-6.92(2H),4.84-4.91(2H),1.07-1.19(12H).

[0127] 13 C-NMR (in CDCl3, d=): 161.3, 148.9, 143.7, 135.9, 134.5, 128.8, 127.9, 125.3, 123.3, 118.8, 118.5, 116.5, 115.4, 77.0, 24.3.

[0128] Example 2

[0129] Synthesis of compound (2):

[0130]

[0131] Place the magnet in a dry 250 ml three-necked flask, evacuate the flask and rinse it with nitrogen three times, add 500 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve, place the three-necked flask in a low-temperature magnetic stirring device, and stir at -20°C for 20 minutes. Take 1.1 ml of n-butyl lithium solution (2.5 mol / L hexane solution) and slowly add it dropwise. After the addition is complete, naturally warm to room temperature and stir to react overnight. Place the three-necked flask in a low-temperature magnetic stirring device and stir at -20°C for 20 minutes. Dissolve 243 mg of titanium tetrachloride in 10 ml of toluene at -20°C and slowly add it dropwise to the three-necked flask. After the addition is complete, naturally warm to room temperature and stir to react overnight. The obtained reaction slurry was filtered through diatomaceous earth, and the filter cake was washed with toluene. The obtained dark red solution was desolventized under vacuum to obtain a dark red solid. 10 ml of cold hexane was added, and after thorough mixing, the obtained slurry was centrifuged and the supernatant was poured out. 10 ml of cold hexane was added again, and after thorough mixing, the obtained slurry was centrifuged and the supernatant was poured out. The obtained solid was desolventized under vacuum to obtain 590 mg of a dark red solid with a molar yield of 91%.

[0132] The structure of the dark red solid was confirmed to be compound (2) by H-NMR and C-NMR.

[0133] Example 3

[0134] Synthesis of compound (2):

[0135] The magnet was placed in a dry 250 ml three-necked flask. The flask was evacuated and flushed with nitrogen three times. 100 mg of compound (1) was added and dissolved in 10 ml of toluene. 500 mg of trimethylsilyl chloride was added and reacted at room temperature overnight. All volatile components such as the solvent were removed in vacuo. Toluene was added to dissolve, and the solution obtained by filtration was sealed under nitrogen and placed in a freezer at -20°C for freezing and crystallization to obtain 79 mg of dark red crystals with a molar yield of 86%.

[0136] The structure of the deep red crystals was confirmed to be compound (2) by H-NMR and C-NMR.

[0137] Example 4

[0138] Synthesis of compound (3):

[0139]

[0140] Place the magnet in a dry 250 ml three-necked flask, evacuate the flask and rinse it with nitrogen three times, add 586 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve, place the three-necked flask in a low-temperature magnetic stirring device, and stir at -20°C for 20 minutes. Take 1.3 ml of n-butyl lithium solution (2.5 mol / L hexane solution) and slowly add it dropwise. After the addition is complete, warm to room temperature naturally and stir to react overnight. Place the three-necked flask in a low-temperature magnetic stirring device and stir at -20°C for 20 minutes. Under nitrogen protection, add 350 mg of zirconium tetrachloride solid to the three-necked flask three times, with an interval of 2 minutes each time. After completion, warm to room temperature naturally and stir to react overnight. The obtained reaction slurry was filtered through diatomaceous earth, and the filter cake was washed with toluene. The obtained red solution was freed of solvent under vacuum to obtain a red solid. 10 ml of cold hexane was added and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. 10 ml of cold hexane was added again and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. The obtained solid was freed of solvent under vacuum to obtain 675 mg of dark red solid with a molar yield of 82%.

[0141] The structure of the dark red solid was confirmed to be compound (3) by H-NMR and C-NMR.

[0142] Example 5

[0143] Synthesis of compound (4):

[0144]

[0145] Place the magnet in a dry 250 ml three-necked flask, and place the reaction flask on a device for magnetic stirring and oil bath heating. After evacuating the three-necked flask, rinse it repeatedly with nitrogen three times. Add 426 mg of 10-hydroxybenzo[H]quinoline, 296 mg of tetra(ethoxy)zirconium, and 20 ml of toluene under a nitrogen atmosphere, and stir evenly at room temperature. Then, under nitrogen protection, add a condenser with room temperature water as the cooling medium. Control the oil bath temperature at 115-130°C and allow the reaction to proceed under toluene reflux for 18 hours. Cool to room temperature, filter the solution, and remove the solvent in vacuum to obtain a light yellow solid or viscous material. Under nitrogen protection, add 10 ml of cold hexane, mix thoroughly, centrifuge the resulting slurry, pour out the supernatant, and remove the solvent from the resulting solid under vacuum to obtain 482 mg of a light yellow solid with a molar yield of 78%.

[0146] The structure of the light yellow solid was confirmed to be compound (4) by hydrogen and carbon nuclear magnetic spectra.

[0147] Example 6

[0148] Synthesis of compound (5):

[0149]

[0150] Place the magnet in a dry 250 ml three-necked flask, evacuate the flask and rinse it with nitrogen three times, add 575 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve, place the three-necked flask in a low-temperature magnetic stirring device, and stir at -20°C for 20 minutes. Take 1.3 ml of n-butyl lithium solution (2.5 mol / L hexane solution) and slowly add it dropwise. After the addition is complete, naturally warm to room temperature and stir to react overnight. Place the three-necked flask in a low-temperature magnetic stirring device and stir at -20°C for 20 minutes. Under nitrogen protection, add 470 mg of zirconium tetrachloride solid to the three-necked flask three times, with an interval of 2 minutes each time. After completion, naturally warm to room temperature and stir to react overnight. The obtained reaction slurry was filtered through diatomaceous earth, and the filter cake was washed with toluene. The obtained red solution was desolventized under vacuum to obtain a red solid. 10 ml of cold hexane was added and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. 10 ml of cold hexane was added again and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. The obtained solid was desolventized under vacuum to obtain 712 mg of dark red solid with a molar yield of 76%.

[0151] The structure of the dark red solid was confirmed to be compound (5) by H-NMR and C-NMR.

[0152] Example 7

[0153] Synthesis of compound (6):

[0154]

[0155] Place the magnet in a dry 250 ml three-necked flask. After the three-necked flask is evacuated, it is repeatedly flushed with nitrogen three times. Under a nitrogen atmosphere, 300 mg of compound (2) is added. 20 ml of toluene is added and stirred at room temperature to dissolve. The three-necked flask is placed in a low-temperature magnetic stirring device and stirred at -20°C for 20 minutes. Take 1.3 ml of benzyl magnesium chloride solution (1 mol per liter of ether solution) and slowly add it dropwise. After the addition is completed, the temperature is naturally raised to room temperature and the reaction is stirred overnight. The obtained reaction slurry is filtered through diatomaceous earth and the filter cake is washed with toluene. The obtained dark red solution is desolventized under vacuum to obtain a dark red solid. 10 ml of cold hexane is added and mixed thoroughly. The obtained slurry is centrifuged and the supernatant is poured out. 10 ml of cold hexane is added again and mixed thoroughly. The obtained slurry is centrifuged and the supernatant is poured out. The obtained solid is desolventized under vacuum to obtain 310 mg of a dark red solid with a molar yield of 85%.

[0156] The structure of the dark red solid was confirmed to be compound (6) by H-NMR and C-NMR.

[0157] Example 8

[0158] Ethylene polymerization using compound (1) as catalyst

[0159] A 250 ml glass polymerization bottle was dried thoroughly, evacuated, and flushed with nitrogen, and repeated three times. Evacuated, filled with ethylene, the ethylene pressure was 1.05 standard atmospheric pressure, 26 ml of toluene, 3 ml of methylaluminoxane toluene solution (containing 5.0 mmol of methylaluminoxane) were added in sequence, stirring and heating were started, and the temperature was set to 70°C. When the temperature rose to 70°C, 1 ml of catalyst toluene solution (containing 5 micromoles of compound (1)) was added, and the timing was started. When ethylene was consumed, ethylene was replenished to keep the ethylene pressure at a constant 1.05 standard atmospheric pressure. After 20 minutes, the ethylene was turned off, the reaction solution was poured into a beaker, 300 ml of anhydrous ethanol and 5 ml of concentrated hydrochloric acid were added, and stirred for 6 hours. The polymer was filtered and dried under vacuum at 60°C for 24 hours to obtain 0.45 g of polymer. The polymerization activity was 270 kg polymer / mol catalyst / hour.

[0160] Example 9

[0161] Ethylene polymerization using compound (1) as catalyst

[0162] A 250 ml glass polymerization bottle was fully dried, evacuated, and flushed with nitrogen, and repeated three times. Evacuated, filled with ethylene, the ethylene pressure was 1.05 standard atmospheric pressure, 27 ml of toluene, 1 ml of triisobutylaluminum toluene solution (containing 1.0 mmol of triisobutylaluminum) were added in sequence, stirring and heating were started, and the temperature was set to 70°C. When the temperature rose to 70°C, 1 ml of catalyst toluene solution (containing 5 micromoles of compound (1)) was added. After 3 minutes, 1 ml of triphenylmethyl tetrakis(pentafluorophenyl)borate toluene solution (containing 7.5 micromoles of triphenylmethyl tetrakis(pentafluorophenyl)borate) was added, and timing was started. When ethylene was consumed, ethylene was replenished to keep ethylene at a constant standard atmospheric pressure of 1.05. After 20 minutes, ethylene was turned off, the reaction solution was poured into a beaker, 300 ml of anhydrous ethanol and 5 ml of concentrated hydrochloric acid were added, stirred for 6 hours, filtered to obtain a polymer, and vacuum dried at 60°C for 24 hours to obtain 0.32 g of a polymer. The polymerization activity was 192 kg polymer / mol catalyst / hour.

[0163] Example 10

[0164] Ethylene polymerization using compound (1) as catalyst

[0165] A 250 ml glass polymerization bottle was dried thoroughly, evacuated, and flushed with nitrogen, and repeated three times. Evacuated, controlled by a solenoid valve, ethylene was charged, and the ethylene pressure was 1.05 standard atmospheric pressure. 26 ml of toluene and 2.5 ml of diethylaluminum chloride toluene solution (containing 2.5 mmol of diethylaluminum chloride) were added in sequence, stirring and heating were started, and the temperature was set to 70°C. When the temperature rose to 70°C, 1 ml of catalyst toluene solution (containing 5 micromoles of compound (1)) was added. After 3 minutes, 0.5 ml of di-n-butylmagnesium toluene solution (containing 0.5 mmol of di-n-butylmagnesium) was added, and timing was started. When ethylene was consumed, ethylene was replenished to keep the ethylene pressure at a constant 1.05 standard atmospheric pressure. After 20 minutes, ethylene was turned off, the reaction solution was poured into a beaker, 300 ml of anhydrous ethanol and 5 ml of concentrated hydrochloric acid were added, and the mixture was stirred for 6 hours. The polymer was filtered and dried under vacuum at 60°C for 24 hours to obtain 0.68 g of polymer. The polymerization activity was 408 kg polymer / mol catalyst / hour.

[0166] Embodiment 11

[0167] Ethylene polymerization using compound (1) as catalyst

[0168] A 100 ml stainless steel polymerization kettle that has been fully dried is heated to 55°C in an empty state and evacuated for 30 minutes. Ethylene is charged to maintain a weak ethylene flow. 30 ml of n-hexane is added, 2.5 ml of diethylaluminum chloride hexane solution (containing 2.5 mmol of diethylaluminum chloride) is added, stirring is started, the temperature is adjusted to 60°C, 1 ml of catalyst toluene solution (containing 2 micromoles of compound (1)) is added, and after 3 minutes, after stabilization at 60°C, 0.5 ml of di-n-butylmagnesium toluene solution (containing 0.5 mmol of di-n-butylmagnesium) is added, and the feed port is closed. The ethylene pressure is adjusted to 9 standard atmospheres. After 30 minutes, the ethylene is turned off, the temperature is lowered, the pressure is slowly released, and the polymer is taken out. The polymer is soaked in 300 ml of anhydrous ethanol, filtered to obtain the polymer, and vacuum dried at 60°C for 24 hours to obtain 7.79 g of polymer. The polymerization activity is 7790 kg polymer / mol catalyst / hour.

[0169] Example 12

[0170] Ethylene polymerization using compound (2) as catalyst

[0171] The method of Example 8 was followed, except that the compound (1) was replaced by the same molar amount of the compound (2), and 0.51 g of polymer was obtained in the same manner. The polymerization activity was 306 kg polymer / mol catalyst / hour.

[0172] Embodiment 13

[0173] Ethylene polymerization catalyzed by compound (2)

[0174] The method of Example 9 was followed, except that the compound (1) was replaced by the same molar amount of the compound (2), and 0.44 g of polymer was obtained in the same manner. The polymerization activity was 264 kg polymer / mol catalyst / hour.

[0175] Embodiment 14

[0176] Ethylene polymerization catalyzed by compound (2)

[0177] The method of Example 10 was followed, except that the compound (1) was replaced by the same molar amount of the compound (2), and 0.85 g of polymer was obtained in the same manner. The polymerization activity was 510 kg polymer / mol catalyst / hour.

[0178] Embodiment 15

[0179] Ethylene polymerization using compound (3) as catalyst

[0180] The method of Example 8 was followed, except that the compound (1) was replaced by the same molar amount of the compound (3), and 0.49 g of polymer was obtained in the same manner. The polymerization activity was 294 kg polymer / mol catalyst / hour.

[0181] Example 16

[0182] Ethylene polymerization using compound (3) as catalyst

[0183] The method of Example 9 was followed, except that the compound (1) was replaced by the same molar amount of the compound (3), and 0.27 g of polymer was obtained in the same manner. The polymerization activity was 162 kg polymer / mol catalyst / hour.

[0184] Embodiment 17

[0185] Ethylene polymerization using compound (3) as catalyst

[0186] The method of Example 10 was followed, except that the compound (1) was replaced by the same molar amount of the compound (3), and 0.88 g of polymer was obtained in the same manner. The polymerization activity was 528 kg polymer / mol catalyst / hour.

[0187] Embodiment 18

[0188] Ethylene polymerization using compound (4) as catalyst

[0189] The method of Example 8 was followed, except that the compound (1) was replaced by the same molar amount of the compound (4), and 0.50 g of polymer was obtained in the same manner. The polymerization activity was 300 kg polymer / mol catalyst / hour.

[0190] Embodiment 19

[0191] Ethylene polymerization using compound (4) as catalyst

[0192] The method of Example 9 was followed, except that the compound (1) was replaced by the same molar amount of the compound (4), and 0.35 g of polymer was obtained in the same manner. The polymerization activity was 270 kg polymer / mol catalyst / hour.

[0193] Embodiment 20

[0194] Ethylene polymerization using compound (4) as catalyst

[0195] The method of Example 10 was followed, except that the compound (1) was replaced by the same molar amount of the compound (4), and 0.91 g of polymer was obtained in the same manner. The polymerization activity was 546 kg polymer / mol catalyst / hour.

[0196] Embodiment 21

[0197] Ethylene polymerization using compound (5) as catalyst

[0198] The method of Example 8 was followed, except that the compound (1) was replaced by the same molar amount of the compound (5), and 0.42 g of polymer was obtained in the same manner. The polymerization activity was 252 kg polymer / mol catalyst / hour.

[0199] Embodiment 22

[0200] Ethylene polymerization using compound (5) as catalyst

[0201] The method of Example 9 was followed, except that the compound (1) was replaced by the same molar amount of the compound (5), and 0.25 g of polymer was obtained in the same manner. The polymerization activity was 150 kg polymer / mol catalyst / hour.

[0202] Embodiment 23

[0203] Ethylene polymerization using compound (5) as catalyst

[0204] The method of Example 10 was followed, except that the compound (1) was replaced by the same molar amount of the compound (5), and 0.88 g of polymer was obtained in the same manner. The polymerization activity was 528 kg polymer / mol catalyst / hour.

[0205] Embodiment 24

[0206] Ethylene polymerization catalyzed by compound (6)

[0207] The method of Example 8 was followed, except that the compound (1) was replaced by the same molar amount of the compound (6), and 0.57 g of polymer was obtained in the same manner. The polymerization activity was 342 kg polymer / mol catalyst / hour.

[0208] Embodiment 25

[0209] Ethylene polymerization catalyzed by compound (6)

[0210] The method of Example 9 was followed, except that the compound (1) was replaced by the same molar amount of the compound (6), and 0.33 g of polymer was obtained in the same manner. The polymerization activity was 198 kg polymer / mol catalyst / hour.

[0211] Embodiment 26

[0212] Ethylene polymerization catalyzed by compound (6)

[0213] The method of Example 10 was followed, except that the compound (1) was replaced by the same molar amount of the compound (6), and 1.15 g of polymer was obtained in the same manner. The polymerization activity was 690 kg polymer / mol catalyst / hour.

[0214] Comparative Example 1

[0215] Ethylene polymerization using zirconocene dichloride as catalyst

[0216] The method of Example 8 was followed, except that the compound (1) was replaced by the same molar amount of zirconocene dichloride, and 0.32 g of polymer was obtained in the same manner. The polymerization activity was 192 kg polymer / mol catalyst / hour.

[0217] Comparative Example 2

[0218] Ethylene polymerization using zirconocene dichloride as catalyst

[0219] The method of Example 9 was followed, except that the compound (1) was replaced by the same molar amount of zirconocene dichloride, and 0.18 g of polymer was obtained in the same manner. The polymerization activity was 108 kg polymer / mol catalyst / hour.

[0220] Comparative Example 3

[0221] Ethylene polymerization using zirconocene dichloride as catalyst

[0222] The method of Example 10 was followed, except that the compound (1) was replaced by the same molar amount of zirconocene dichloride, and 0.01 g of polymer was obtained in the same manner. The polymerization activity was 6 kg polymer / mol catalyst / hour.

[0223] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A transition metal compound, characterized in that The structure of the transition metal compound is shown in the following formula (1): In formula (1), M is a tetravalent transition metal atom; X and Y are each independently a hydrocarbyloxy group having 1 to 10 carbon atoms, a hydrocarbon group having 1 to 10 carbon atoms, or a halogen.

2. The transition metal compound according to claim 1, wherein M is a titanium atom, a zirconium atom or a hafnium atom, and is preferably a titanium atom or a zirconium atom.

3. The transition metal compound according to claim 1, wherein X and Y are each independently a hydrocarbonoxy group having 1 to 6 carbon atoms, a hydrocarbon group having 1 to 7 carbon atoms, a fluorine atom, a chlorine atom, a bromine atom or an iodine atom; Preferably, X and Y are each independently a hydrocarbyloxy group having 1 to 3 carbon atoms, a hydrocarbon group having 1 to 3 carbon atoms, or a chlorine atom; Preferably, the alkoxy group having 1 to 10 carbon atoms is methoxy, ethoxy, propoxy or isopropoxy; Preferably, the hydrocarbon group having 1 to 10 carbon atoms is methyl, ethyl, propyl, isopropyl or benzyl.

4. The transition metal compound according to any one of claims 1 to 3, wherein X and Y are both isopropoxy or ethoxy; or, X and Y are both chlorine atoms.

5. A catalyst composition, characterized in that The catalyst composition comprises the following components: a) the transition metal compound according to any one of claims 1 to 4; b) Co-catalyst component.

6. The catalyst composition according to claim 5, wherein The co-catalyst component includes an alkylaluminoxane, a combination of an organic boron compound and an organic aluminum compound, or a combination of an organic aluminum compound and an organic magnesium compound; Preferably, the co-catalyst component is an alkylaluminoxane, a combination of an organic boron compound and an organic aluminum compound, or a combination of an organic aluminum compound and an organic magnesium compound.

7. The catalyst composition according to claim 6, wherein The alkylaluminoxane is a compound selected from the group consisting of compounds represented by formula (2) and / or formula (3), In formula (2) and formula (3), R is selected from an alkyl group having 1 to 15 carbon atoms, and n represents an integer of 4 to 30; Preferably, R is selected from an alkyl group having 1 to 5 carbon atoms, and n represents an integer of 10 to 30; Preferably, the alkylaluminoxane is methylaluminoxane.

8. The catalyst composition according to claim 6, wherein The organic boron compound is one or more of triphenylmethyl tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and tris(pentafluorophenyl)boron.

9. The catalyst composition according to claim 6, wherein The organoaluminum compound is a compound having a structure represented by the general formula AlX1X2X3, wherein X1, X2 and X3 are respectively a halogen atom, an alkyl group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, and an aryloxy group having 6 to 12 carbon atoms, and X1, X2 and X3 may be the same or different, and at least one of them is an alkyl group having 1 to 8 carbon atoms; Preferably, the organoaluminum compound is triisobutylaluminum.

10. The catalyst composition according to claim 6, wherein The organomagnesium compound is an organomagnesium compound containing two alkyl groups with carbon atoms of 1 to 10, preferably an organomagnesium compound containing two alkyl groups with carbon atoms of 1 to 6, and more preferably di-n-butylmagnesium.

11. The catalyst composition according to claim 6, wherein The co-catalyst component is alkylaluminoxane, and the molar ratio of the transition metal compound to the alkylaluminoxane calculated on the basis of aluminum is 1:(100-20000), preferably 1:(200-10000), and more preferably 1:(500-5000).

12. The catalyst composition according to claim 6, wherein The co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, the molar ratio of the transition metal compound to the organic boron compound is 1:(1-5), preferably 1:(1-2), the molar ratio of the transition metal compound to the organic aluminum compound is 1:(10-5000), preferably 1:(50-1000), more preferably 1:(100-500).

13. The catalyst composition according to claim 6, wherein The co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, the molar ratio of the transition metal compound to the organoaluminum compound is 1:(30-5000), preferably 1:(100-1000), more preferably 1:(100-500), and the molar ratio of the transition metal compound to the organomagnesium compound is 1:(10-2000), preferably 1:(100-1000); Preferably, the molar ratio of the organoaluminum compound to the organomagnesium compound is greater than 2.5:

1.

14. An olefin polymerization method, characterized in that: The method comprises contacting olefin with the catalyst composition described in any one of claims 5 to 13 to carry out polymerization reaction.

15. The method according to claim 14, wherein: The concentration of the transition metal compound in the polymerization reaction system is 1×10 -10 mol / L~1×10 -3 mol / L, preferably 1×10 -8 mol / L~1×10 -5 mol / L.

16. The method according to claim 14, wherein: The polymerization temperature is -50 to 200°C, and the polymerization time is 1 to 300 minutes; Preferably, the polymerization temperature is -20 to 150° C., and the polymerization time is 5 to 60 minutes.

17. The method according to claim 14, wherein: The partial pressure of the olefin is 0.1-10 MPa, preferably 0.1-4.0 MPa.

18. Use of the transition metal compound according to any one of claims 1 to 4 or the catalyst composition according to any one of claims 5 to 13 in olefin polymerization.